Negative electrode-glass electrolyte laminate, all-solid-state secondary battery

By laminating lithium metal foil to sulfide glass electrolyte layer at high homogeneous temperatures, forming a negative electrode-glass electrolyte laminate, the problem of insufficient bonding strength between lithium metal foil and solid electrolyte layer is solved, and a low interface resistance and stable battery is achieved performance.

CN119301766APending Publication Date: 2025-01-10SK ON CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042516.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When the lithium metal foil is directly laminated to the solid electrolyte layer, the layer bonding strength is insufficient, resulting in a large interface resistance and affecting battery performance.

Method used

The lamination technology at high homogeneous temperature is adopted to allow the natural film on the surface of the lithium metal foil to be absorbed by the reactive laminate layer to form a negative electrode-glass electrolyte laminate, ensuring that the interface resistance is small when no pressure is applied and passes through the thermal layer. The pressure process is laminated at a homogeneous temperature of 0.85 to <1, controlling the thickness and interface resistance of the laminated layer.

Benefits of technology

Excellent bonding strength between the negative electrode and the glass electrolyte layer is achieved, interface resistance is reduced, further oxidation reaction is avoided, and the stability and performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301766A_ABST
    Figure CN119301766A_ABST
Patent Text Reader

Abstract

Disclosed are a negative electrode-glass electrolyte layer laminate, an all-solid-state secondary battery including the negative electrode-glass electrolyte layer laminate, and a method of manufacturing the negative electrode-glass electrolyte layer laminate. The negative electrode-glass electrolyte layer laminate includes a negative electrode and a glass electrolyte layer on at least one surface of the negative electrode, in which the negative electrode includes a surface-passivated lithium-containing metal foil, and the laminate is electrochemically operable without external pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention was made with government support under Award No. DE-AR0000772 awarded by the Advanced Research Projects Agency-Energy (ARPA-E) of the U.S. Department of Energy. The Government has certain rights in this invention.

[0002] The present invention relates to a negative electrode-glass electrolyte laminate, an all-solid-state secondary battery including the laminate, and a method for manufacturing the same. Background Art

[0003] All-solid-state secondary batteries generally include a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode. The solid electrolyte layer includes a solid electrolyte, and the positive electrode and the negative electrode include active materials and a common solid electrolyte, respectively.

[0004] All-solid-state secondary batteries have a lower risk of explosion or fire than batteries containing liquid electrolytes, and are attracting attention as next-generation secondary batteries due to their potential for high energy density.

[0005] In particular, solid-state batteries based on lithium metal as the negative electrode active material are particularly promising. Lithium metal is an ideal material for batteries due to its high theoretical capacity (3.86Ah / g), low density and electropositivity (-3.04V vs. SHE). Lithium metal primary cells are known for their unique high battery voltage (>3 volts), compactness and light weight. It is well known that lithium metal foil is surface passivated even when the foil is formed in an oxygen-deficient environment because metallic lithium spontaneously reacts with oxygen to form a natural oxide surface film. The advantage of the natural film is that it provides the necessary surface passivation to prevent oxidative degradation during storage and downstream processing. However, in some cases, the presence of the natural oxide film may adversely affect battery performance and often cause difficulties in layer bonding (for example, when trying to bond or laminate lithium metal foil and solid electrolyte layers). Summary of the invention

[0006] Technical issues

[0007] Thus, the present invention solves the layer adhesion problems associated with laminating lithium metal foil directly to a solid electrolyte layer.

[0008] Technical solutions to technical problems

[0009] In one aspect, the present invention provides a negative electrode consisting of a surface-passivated lithium-containing metal foil laminated at high homologous temperature (HHT-laminated) to a sulfide glass electrolyte layer, the negative electrode having excellent adhesive strength between the glass electrolyte layer and the lithium-containing metal foil. According to the present invention, lamination is performed in a manner and at a sufficiently high homologous temperature of the metal foil so that any native film (e.g., oxide, carbonate or combination thereof) on the surface of the foil is absorbed by what is referred to herein as a "laminating layer" reactively formed at the interface.

[0010] The lamination layer should not impart an excessive interfacial resistance, specifically, the laminate thus formed has a small interfacial resistance even in a state where no pressure is applied. The term surface passivation is used to mean that the lithium-containing metal foil has an oxidized or carbonated surface (i.e., a native oxide and / or carbonate film) in its pre-laminated state, which substantially prevents further reaction when stored or handled in an oxygen-deficient environment. According to the present invention, due to lamination at a sufficiently high homologous temperature of at least 0.85, in particular below the crystallization temperature of the glass electrolyte layer, the native film is absorbed by the lamination layer formed at the interface between the lithium-containing metal foil and the glass electrolyte layer.

[0011] When the term "homologous temperature" is used, it means the homologous temperature of the lithium-containing active material of the negative electrode, which is useful in this article because it uses the Kelvin scale to express the temperature of a material as a fraction of its melting point temperature. Thus, this allows comparison of the operating conditions of different lithium-containing metal foils and is therefore related to the diffusion dependent deformation that may occur when laminating at high temperatures (e.g., close to the melting point of the metal foil). Therefore, when referring to a laminate formed at a homologous temperature of at least 0.85 and less than 1, the term HHT-lamination (HHT-laminate) is sometimes used herein and in the claims.

[0012] Another aspect of the present invention can provide a method for manufacturing a negative electrode-glass electrolyte layer laminate, wherein the glass electrolyte membrane and the lithium-containing metal foil are at a homologous temperature between 0.85 and <1 (for example, for lithium metal foil, the temperature range is 120° C. to 180° C.), while at about 0.05 kgf / cm 2 Up to 0.3kgf / cm 2In various embodiments, the laminating step is performed in an inert non-vacuum environment, such as a chamber or a drying oven filled with argon. In a specific embodiment, the natural film on the surface of the lithium metal foil is sufficiently robust and the lamination temperature is sufficiently high so that the lamination step can be performed in a dry indoor environment of ambient air with a low moisture content (e.g., a dew point below -40°C). In various embodiments, the natural oxide film is controllably formed before lamination. For example, the original (as-received) lithium-containing metal foil or the nascent (as-formed) lithium-containing metal foil is pretreated by abrading the surface in a manner that exposes fresh lithium metal to an environment containing gaseous oxygen before lamination to form a controlled native oxide film, typically with a thickness of between 100nm and 1μm.

[0013] In various embodiments, the method involves melting and wetting lithium metal to form a lithium metal layer, and before the lithium metal layer is completely cooled, laminating the lithium metal layer to a glass electrolyte membrane at a sufficiently high homologous temperature (e.g., 0.85 to <1) by simply placing a solid electrolyte on the lithium metal surface and applying slight pressure.

[0014] According to one aspect of the present invention, the negative electrode-glass electrolyte layer laminate may include a negative electrode and a glass electrolyte layer on at least one surface of the negative electrode, wherein the negative electrode includes a lithium-containing metal foil having a native film, the native film being sufficiently absorbed and / or pushed back into the depth of the Li foil by the laminate layer so that when the pressure applied to the negative electrode-glass electrolyte layer laminate is 0 kgf / cm 2 When the laminate is used, it can be used in a battery cell.

[0015] The negative electrode-glass electrolyte layer laminate may satisfy the following formula (1):

[0016] [|(R1-R2)| / R1]Х100≤10%(1)

[0017] R2 is the pressure applied to the negative electrode-glass electrolyte layer laminate of 0.3 kgf / cm 2 The interface resistance between the negative electrode and the glass electrolyte layer.

[0018] Specifically, the lamination step is conducted at sufficiently high homologous temperature and pressure so that diffusion-dependent deformation effectuates an anode-glass electrolyte layer laminate that is free of pores at the interface between the anode and the glass electrolyte layer.

[0019] The interface between the negative electrode and the glass electrolyte layer may include what is referred to herein as a laminating layer, which is formed by the reaction of the lithium-containing metal with the sulfide-based glass electrolyte.

[0020] The thickness of the laminate layer is not particularly limited. It can range from about greater than 0 μm to about 30 μm or less. For example, greater than 0 μm, 0.001 μm or more, 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 1 μm or more, 3 μm or more, or 5 μm or more and 30 μm or less, such as 25 μm or less, 20 μm or less, 17 μm or less, or 15 μm or less. For example, the thickness of the laminate layer can be about 20 μm.

[0021] The glass electrolyte layer may be a monolithic electrolyte layer. The thickness of the glass electrolyte layer may be 1 μm or more, such as 3 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 50 μm or more, or 100 μm or more and 1000 μm or less, such as 800 μm or less, 700 μm or less, 500 μm or less, 300 μm or less, or 200 μm or less. For example, the thickness of the glass electrolyte layer may be about 200 μm, about 100 μm, about 50 μm, about 30 μm, about 20 μm, or about 10 μm.

[0022] The glass electrolyte layer may be sulfide based.

[0023] The glass electrolyte layer may include Li, S, P, Si, As, and B.

[0024] In various embodiments, a method for manufacturing a negative electrode-glass electrolyte layer involves a hot lamination process, which includes: providing a surface-passivated lithium-containing metal foil and laminating the foil onto a sulfide-based glass electrolyte membrane, heating and pressing at a homologous temperature greater than about 0.85 and <1 to laminate the lithium-containing metal foil and the sulfide-based glass electrolyte membrane.

[0025] Lamination may be performed at a temperature of 140°C to 180°C.

[0026] Can be 0.05kgf / cm 2 Up to 0.3kgf / cm2 Lamination is performed under pressure.

[0027] Lamination can be performed for 5 to 30 minutes. In various embodiments, lamination is performed for less than 1 minute (e.g., about 60 seconds or about 50 seconds or about 40 seconds or about 30 seconds or about 20 seconds or about 10 seconds or about 5 seconds).

[0028] In various embodiments, fast HHT lamination is performed using a high homologous temperature close to 1 (e.g., >0.9) for a time of about 5 seconds or less (e.g., about 5 seconds or about 4 seconds or about 3 seconds or about 2 seconds or about 1 second or about 500 milliseconds). For example, fast lamination is performed at a homologous temperature between 0.95 and <1 for a time of 5 milliseconds to 1000 milliseconds. Due to the high homologous temperature of the fast lamination step, the lamination pressure can be minimized. In various embodiments, by 2 To <1kgf / cm 2 The laminate is formed by rapid lamination under a pressure within a range of 1000 to 2000 rpm.

[0029] The lamination step is typically performed in an oxygen-deficient environment, such as an inert non-vacuum environment (e.g., a chamber filled with argon or a drying box). However, the present invention is not limited thereto, and it is contemplated that the lamination step is sufficiently robust to allow the layers to be laminated in an air environment (e.g., a drying room with sufficiently low moisture content).

[0030] In various embodiments, the original (as-received) lithium metal foil or lithium-containing metal foil is treated by abrading the surface to remove and reform the natural film in a controlled manner. For example, the lithium surface is abraded and then exposed to a controllable atmosphere for a period of time. Specifically, the lamination step is performed essentially immediately after the natural film is formed. In various embodiments, the controllable atmosphere has a very low moisture content (e.g., <10ppm H2O). In other embodiments, the atmosphere is a low oxygen environment such as a drying chamber filled with air with a dew point <40°C. According to another aspect of the present invention, an all-solid-state secondary battery may include: a negative electrode-glass electrolyte layer laminate and a positive electrode as described herein.

[0031] The all-solid-state secondary battery may further include a solid electrolyte layer between the glass electrolyte layer of the negative electrode-glass electrolyte layer laminate and the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and other aspects, features and other advantages of the present invention will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which:

[0033] Figure 1 is a diagram schematically showing a cross section of a negative electrode-glass electrolyte layer laminate according to an exemplary embodiment;

[0034] Figure 2 is a diagram schematically showing a cross section of a conventional powder pressurized cell in which a lithium metal negative electrode and a sulfide-based electrolyte layer are in contact with each other;

[0035] Figure 3 is a diagram schematically showing a method for manufacturing a negative electrode-glass electrolyte layer laminate by laminating a lithium-containing metal foil and a glass electrolyte membrane by heating and pressurizing in Example 1;

[0036] Figure 4 are SEM photographs of the cross section of the negative electrode-glass electrolyte layer laminate according to Example 1, taken at magnifications of 400 times (a), 1000 times (b), and 2000 times (c), respectively;

[0037] Figure 5 : is a graph showing the change in interface resistance variation factor with pressure measured for the negative electrode-glass electrolyte laminate manufactured in Example 1 and the contact structure manufactured in Comparative Example 1 in which the negative electrode and the glass electrolyte layer are in contact with each other. DETAILED DESCRIPTION

[0038] Hereinafter, exemplary embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0039] In this specification, unless otherwise defined, all technical terms and scientific terms have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein are only for effectively describing a particular example and are not intended to limit the present invention.

[0040] Singular forms used in this specification may be intended to include plural forms as well, unless the context indicates otherwise.

[0041] The numerical range used in this specification includes upper and lower limits and all values ​​within these upper and lower limits, increments of form and span logical deduction within the limited range, all double limit values ​​(double limited value), and all possible combinations of upper and lower limits within the numerical range defined in different forms. Unless otherwise defined in this specification, values ​​that may exceed the numerical range due to experimental error or rounding of numerical values ​​are also included in the defined numerical range.

[0042] The term "comprising" in this specification is an open description, which has a meaning equivalent to terms such as "having", "including", "having" or "characterized by", and does not exclude elements, materials or steps not further described herein.

[0043] The term “A and / or B” in the present specification may refer to an embodiment including both A and B or may refer to an embodiment in which one of A and B is selected.

[0044] In the present specification, it should be understood that when an element such as a layer, film, region, or substrate is referred to as being “on” or “above” another element, it can be directly on the other element or intervening elements may be present therebetween.

[0045] The exemplary embodiment provides a negative electrode-glass electrolyte layer laminate in which a negative electrode and a glass electrolyte membrane are laminated together, Figure 1 An example of a negative electrode-glass electrolyte layer laminate is schematically shown in FIG.

[0046] refer to Figure 1 The negative electrode-glass electrolyte layer laminate 20 (hereinafter also referred to as a "laminate") may include a negative electrode 21 and a glass electrolyte layer 25 on at least one surface of the negative electrode 21. Specifically, the glass electrolyte layer 25 may be laminated on at least one surface of the negative electrode 21. The negative electrode 21 may be a lithium-containing metal negative electrode, specifically, may include a lithium-containing metal foil. The glass electrolyte layer 25 is based on a sulfide, however, alternative compositions including oxides may be considered, for example, may be based on a sulfide.

[0047] Specifically, the glass electrolyte layer 25 may be laminated on one surface of the lithium-containing metal negative electrode, and more specifically, a sulfide-based glass electrolyte layer may be laminated on one surface of the lithium-containing metal negative electrode.

[0048] As an example, the lithium-containing metal foil may be a foil made of lithium metal alone, or may be an alloy foil of lithium and other metals, for example, there is no limitation thereto, as long as it can be used as a negative electrode in a secondary battery containing a sulfide-based solid electrolyte. The metal forming an alloy with lithium may be, but is not limited to, a metal selected from elements of Group 13, Group 14, and Group 15 of the periodic table, specifically, In, Al, Sn, Si, Mg, Zn, Ge, Ag, etc., any of which may form an alloy with lithium, and two or more metals may form an alloy with lithium.

[0049] For example, the negative electrode 21 may not include a particulate negative electrode active material. More specifically, the negative electrode may not include a particulate negative electrode precipitate, wherein the negative electrode precipitate may include dendrites. When the negative electrode includes a particulate negative electrode active material, pores appear in the negative electrode or on the surface of the negative electrode due to the presence of the particulate negative electrode active material, resulting in point contact between the particulate negative electrode active material and the glass electrolyte layer, so that the reaction active area cannot be fully ensured in the interface between the negative electrode and the glass electrolyte layer, increasing the interface resistance.

[0050] The glass electrolyte layer 25 is a monolithic electrolyte layer having no pores therein. No interface resistance occurs inside the glass electrolyte layer 25, thereby providing excellent lithium ion conductivity.

[0051] The glass electrolyte layer 25 may be based on sulfide, and the specific composition is not particularly limited as long as it can contain sulfur atoms in the electrolyte composition and form an amorphous state. In addition, the glass electrolyte may be a crystallized glass electrolyte (ie, glass ceramic) or a completely amorphous glass electrolyte.

[0052] The sulfide-based electrolyte forming the glass electrolyte layer 25 may include Li, S, P, Si, B, and As, and specifically, may be LPS-type sulfide containing sulfur and phosphorus, Li 4-x Ge 1-x P x S4 (x is 0.1 to 1, specifically, x is 3 / 4, 2 / 3), Li 10±1 MP2X 12 (M = Ge, Si, Sn, Al, X = S, Se), Li 3.833 Sn 0.833 As 0.166 S4, Li4SnS4, Li 3.25 Ge 0.25 P 0.75 S4, a combination of Li2S and one or more of P2S5, B2S3, SiS2 and GeS2, xLi2S-(100-x)P2S5 (x is 70 to 80), Li2S-SiS2-Li3N, Li2S-P2S5-LiI, Li2S-SiS2-LiI, Li2S-B2S3-LiI, etc., but not limited to these.

[0053] exist Figure 2, an example of a powder pressurized battery cell 10 is schematically shown, in which a particulate solid electrolyte layer 15 including a particulate solid electrolyte is formed on the surface of a lithium metal-containing negative electrode 11 .

[0054] refer to Figure 2 , the granular solid electrolyte layer 15 may have a plurality of pores 17 formed therein, and the interfacial resistance in the granular solid electrolyte layer 15 may be increased by the pores 17. In addition, the point contact formed in the interface between the lithium-containing metal negative electrode 21 and the granular solid electrolyte layer 15 may increase the interfacial resistance, and the bonding strength between the lithium-containing metal negative electrode 11 and the granular solid electrolyte layer 15 may not be sufficiently obtained, thereby causing interlayer separation.

[0055] Therefore, in order to solve the problems of large interface resistance and interlayer delamination inside the granular solid electrolyte layer 15 and at the interface between the lithium-containing metal negative electrode 11 and the granular solid electrolyte layer 15, it is necessary to continuously pressurize the battery (battery) with the powder pressurized battery cell 10 containing the lithium metal negative electrode and the granular solid electrolyte layer to maintain interface contact during battery driving.

[0056] For example, an all-solid-state secondary battery including a conventional granular solid electrolyte layer 15 needs to apply or maintain 5 tons / cm during electrode manufacturing, battery manufacturing, or battery driving. 2 The compressive stress is above 100° to minimize the resistance of the electrochemical reaction occurring in the interface between the electrode and the electrolyte layer.

[0057] However, the laminate 20 according to the exemplary embodiment has improved contact between the negative electrode 21 (specifically, the negative electrode 21 including the lithium metal foil) and the glass electrolyte layer 25, thereby reducing the interface resistance and driving the battery without separate pressing. Therefore, since an additional pressing device (additional pressing means) for battery driving in electric vehicles and the like may not be required, a pressing restraint device is not required, so that weight can be reduced, loading efficiency can be increased, and space utilization can be increased.

[0058] More specifically, the laminate 20 is integrated by laminating the glass electrolyte layer 25 on the negative electrode containing lithium metal foil, thereby having excellent bonding at the interface and reducing interlayer separation problems. Integration means that the two layers can be laminated at the interface without using a separate adhesive at the interface between the negative electrode containing lithium metal foil and the glass electrolyte layer 25.

[0059] A method of manufacturing the laminate 20 according to the exemplary embodiment will be described below.

[0060] Conventionally, when a lithium-containing metal foil is laminated with a sulfide-based solid electrolyte (amorphous or crystalline) without heating, the bonding strength of the resulting laminate is insufficient, and a uniform insertion and desorption process of lithium ions may not occur during charge and discharge, resulting in the formation of dendrites. In addition, the lithium-containing metal foil is easily delaminated with the glass electrolyte membrane. Therefore, a method of continuously providing pressure in the battery may be required for maintaining the interfacial contact between the lithium-containing metal foil and the glass electrolyte membrane.

[0061] The negative electrode-glass electrolyte layer laminate according to the exemplary embodiment may be manufactured by the following method. Figure 3 The concept of manufacturing a laminate according to an exemplary embodiment is schematically illustrated.

[0062] refer to Figure 3 In the negative electrode-glass electrolyte layer laminate 20 according to the exemplary embodiment, a lithium-containing metal foil and a glass electrolyte membrane 31 are layered on a lithium-containing metal foil 35. The lithium-containing metal foil 35 and the glass electrolyte membrane 31 may be as described above for the negative electrode 21 and the glass electrolyte layer 25 of the laminate 20, respectively, and the shapes of the lithium-containing metal foil 35 and the glass electrolyte membrane 31 are not particularly limited, and shapes molded into the shape of the electrode to be provided may be used.

[0063] Next, the laminated body 20 in which the lithium-containing metal foil 35 and the glass electrolyte membrane 31 are laminated is manufactured.

[0064] like Figure 3 As shown, lamination is performed using a heating plate including an upper plate 41 and a lower plate 43. The heating plate can heat the upper plate 41 and the lower plate 43 to a predetermined high homologous temperature and press to laminate the lithium-containing metal foil 35 directly on the glass electrolyte membrane 31.

[0065] Specifically, in various embodiments, the lithium-containing metal foil 35 and the glass electrolyte membrane 31 are heated and pressurized on both the upper and lower sides, which heating and pressurization are different from pressurization in the following state: the upper plate 41 or the lower plate 43 of the heating plate on the side of the lithium-containing metal foil 35 is heated to mold the lithium metal into a predetermined shape.

[0066] The heating plate is not particularly limited as long as it can heat both sides of the upper plate 41 and the lower plate 43 , and the heating plate can be used appropriately as long as it includes a heating device to heat both sides of the upper plate 41 and the lower plate 43 of the heating plate.

[0067] Furthermore, pressurization may be performed by applying pressure by moving any one of the upper plate 41 and the lower plate 43 or by moving the upper plate 41 and the lower plate 43 so that the plates face each other.

[0068] The heating for lamination is performed at a high homogenous temperature in the range of 0.85 to <1. For example, for lithium metal foil, the heating for lamination can be performed at a temperature of 120°C or more, specifically 130°C or more, more specifically 140°C or more, and at a temperature of 180°C or less, specifically 170°C or less, more specifically 165°C or less. When the heating temperature is lower than 120°C (or the homogenous temperature is lower than 0.85), the lithium-containing metal foil 35 is not softened, so it may be difficult to laminate the foil with the glass electrolyte membrane 31; when the heating temperature is higher than 180°C (i.e., the homogenous temperature is higher than 1), the lithium-containing metal foil 35 may melt and flow, and in addition, the glass electrolyte membrane 31 may crystallize, thereby deteriorating the conductivity of lithium ions.

[0069] The pressure applied for lamination is not particularly limited, but may be 0.01 kgf / cm 2 Above, specifically 0.3kgf / cm 2 More specifically, 0.05 kgf / cm 2 Above and 3kgf / cm 2 Below, specifically 1kgf / cm 2 More specifically, 0.5 kgf / cm 2 More specifically, 0.3 kgf / cm 2 When the applied pressure is less than 0.01kgf / cm 2 When the pressure is higher than 3kgf / cm 2 When the electrolyte is heated, cracks may appear on the glass electrolyte membrane.

[0070] The lamination time by heating and pressurizing can be adjusted by the thickness of the lithium-containing metal foil 35 and the glass electrolyte membrane 31, and although not particularly limited, can be 5 minutes to 30 minutes. When the lamination time is less than 5 minutes, sufficient interface lamination may not be completed between the lithium-containing metal foil 35 and the glass electrolyte membrane 31; when the lamination time exceeds 30 minutes, the lithium-containing metal foil 35 may melt.

[0071] Since the glass electrolyte membrane 31 has low wettability to the lithium-containing metal foil 35, when the lithium-containing metal foil 35 melts, the lithium-containing metal foil 35 is not laminated in the interface with the glass electrolyte membrane 31 while maintaining a plate shape, and the lithium-containing metal foil 35 may bend and curl.

[0072] As an example, the glass electrolyte membrane 31 and the lithium-containing metal foil 35 are laminated by heating and pressurizing up and down to soften the lithium-containing metal foil 35 to form a laminate layer in the interface between the lithium-containing metal foil 35 and the glass electrolyte membrane 31, and the lithium-containing metal foil 35 and the glass electrolyte membrane 31 are integrated through the laminate layer to form a negative electrode-glass electrolyte layer laminate 20 in which two layers are firmly laminated.

[0073] In the negative electrode-glass electrolyte layer laminate 20 according to the exemplary embodiment, although the thickness of the negative electrode 21 and the glass electrolyte layer 25 is not particularly limited, for example, the thickness of the negative electrode 21 may be 1 μm or more, for example, 3 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 50 μm or more and 1000 μm or less, for example, 700 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, or 100 μm or less. In addition, the thickness of the glass electrolyte layer 25 may be 1 μm or more, for example, 3 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 50 μm or more, or 100 μm or more and 1000 μm or less, for example, 800 μm or less, 700 μm or less, 500 μm or less, 300 μm or less, or 200 μm or less.

[0074] In various embodiments, the lithium-containing metal foil is a lithium metal foil. For example, it can be a lithium foil extruded from a lithium ingot as a separate lithium metal foil or a lithium foil extruded from or subsequently contacted with a current collecting foil, typically a copper foil (e.g., having a thickness of about 5 μm to 15 μm).

[0075] In various embodiments, the laminate is formed by flash lamination at a high homologous temperature in the range of 0.9 to <1 (eg, close to but less than 1).

[0076] Figure 4 2 shows a cross section of a negative electrode-glass electrolyte layer laminate 20 according to an exemplary embodiment. Figure 4 These are SEM photographs of a cross section of a laminate 20 of Example 1 described later, taken at magnifications of 400 times (a), 1000 times (b), and 2000 times (c), respectively.

[0077] refer to Figure 4As shown in each SEM photograph in FIG. 1 , the laminate 20 includes a negative electrode 21 containing lithium metal and a glass electrolyte layer 25, wherein a laminate layer 23 in which lithium metal and a glass electrolyte are mixed by softening lithium metal is included in the interface between the negative electrode 21 and the glass electrolyte layer 25, and the negative electrode 21 and the glass electrolyte layer 25 can be laminated by the laminate layer 23. Thus, the laminate layer is composed of elemental components of the sulfide glass electrolyte, particularly sulfur, and lithium and other elements of a natural film generally on the surface of lithium, including one or more of oxygen and carbon (e.g., oxygen).

[0078] Specifically, the laminate layer 23 as well as the negative electrode 21 and the glass electrolyte layer 25 may not have pores.

[0079] Although the thickness of the laminate layer 23 is not particularly limited, it may be 0.1 μm or more, for example 0.3 μm or more, 0.5 μm or more, 1 μm or more, 3 μm or more, or 5 μm or more and 30 μm or less, for example 25 μm or less, 20 μm or less, 17 μm or less, or 15 μm or less.

[0080] As an example, the laminate 20 has no particles in the negative electrode 21 and the glass electrolyte layer 25, so that there are no pores in the negative electrode 21 and the glass electrolyte layer 25 and when the two layers are laminated by the lamination layer 23, there are no pores in the interface and the lamination layer 23, thereby maintaining the interface resistance between the two layers at a low value and the laminate can be electrochemically operated.

[0081] Furthermore, according to the present exemplary embodiment, when the laminate 20 is not pressurized (0 kgf / cm 2 ) and when 0.3 kgf / cm is applied to the laminate 20 2 The change rate of the interface resistance (R2) between the negative electrode 21 and the glass electrolyte layer 25 when the pressure is greater than 20°C can satisfy the following formula (1):

[0082] [|(R1-R2)| / R1]Х100≤10%(1).

[0083] In this way, the laminate 20 has excellent bonding strength between the negative electrode 21 and the glass electrolyte layer 25, so that the interface resistance can be very low, and the change in interface resistance before and after pressurization can be very small. Specifically, the peel strength of the laminate is greater than the tensile strength of lithium metal. Therefore, when the laminate 20 is used, the battery can be driven continuously even in the case where a device for maintaining a separate pressure is not provided during battery evaluation and battery driving.

[0084] In addition, in an exemplary embodiment, the positive electrode is layered on the laminate 20 in which the negative electrode 21 and the glass electrolyte layer 25 are laminated, thereby manufacturing an all-solid-state secondary battery, specifically, manufacturing an all-solid-state secondary battery including a sulfide-based solid electrolyte. The positive electrode can be placed on the glass electrolyte layer 25 of the laminate 20. In addition, if necessary, a solid electrolyte layer can also be included between the positive electrode and the laminate 20, wherein the solid electrolyte layer can be based on an oxide or a sulfide, but is not limited thereto.

[0085] The present invention is described in detail below by way of examples. The following examples are used to specifically illustrate the present invention, but the present invention is not limited thereto.

[0086] Example 1

[0087] A lithium metal foil having a thickness of 200 μm was die cut into a circular shape having a diameter of 6 mm.

[0088] Two circular lithium ion conducting sulfide-based glass electrolyte discs having a thickness of 500 μm and a diameter of 10 mm were prepared.

[0089] In the main glove box filled with argon, lithium metal foils were placed on the upper and lower parts of the sulfide-based glass electrolyte membrane, and circular copper foil current collectors with a thickness of 15 μm and a diameter of 6 mm were placed on both sides, placed between a pair of heating plates (SUS), and heated at a homogenous temperature slightly lower than 1 (about 175 °C) and 0.2 kgf / cm 2 The battery was heated and pressed at a pressure of 100° for 30 minutes to produce a symmetrical battery cell in which sulfide-based glass electrolyte layers were laminated on the upper and lower parts of the lithium metal anode.

[0090] The cross-section of the lithium metal anode and the sulfide-based glass electrolyte layer in the symmetrical battery cell thus fabricated was photographed by SEM. Figure 4 shown. Figure 4 (a), 4(b), and 4(c) are SEM images taken at magnifications of 400x, 1000x, and 2000x, respectively.

[0091] from Figure 4 As can be seen from the individual SEM photographs in , in the laminate obtained in Example 1, it was found that the lithium metal negative electrode and the sulfide-based glass electrolyte layer were laminated by softening of the lithium metal between the lithium metal negative electrode and the sulfide-based glass electrolyte layer. In addition, it was found that the laminated layer and the lithium metal negative electrode and the sulfide-based glass electrolyte layer had no pores.

[0092] Comparative Example 1

[0093] The same current collector and lithium metal foil as in Example 1 were used, but the lithium metal foil was arranged on the current collector, followed by pressurization and lamination to manufacture two sheets of laminated bodies of the current collector and the lithium metal foil.

[0094] The laminate of the current collector and the lithium metal foil manufactured as above was arranged so that the lithium metal foil was in contact with both sides of the sulfide-based glass electrolyte membrane same as in Example 1 and placed between heating plates, except that the lithium metal foil and the sulfide-based electrolyte membrane were heated at 0.2 kgf / cm 2 A symmetrical cell was manufactured in the same manner as in Example 1, except that the contact structure was manufactured by pressing at a pressure of 1000 nm for only 30 minutes without heating.

[0095] Measurement of interface resistance

[0096] Change the pressure to 0kgf / cm 2 (Unpressurized), 0.1kgf / cm 2 , 0.2kgf / cm 2 and 0.3kgf / cm 2 At the same time, for the symmetrical cells obtained in Example 1 and Comparative Example 1, the interface resistance between the lithium metal negative electrode and the sulfide-based electrolyte layer was measured. The results are as follows Figure 5 shown.

[0097] The interface resistance was measured using a potentiostat equipment provided by BioLogic Sciences Instruments. The measurement conditions were set to apply an AC voltage of 10 mV in a frequency range of 0.1 Hz to 7 MHz.

[0098] Comparison of interface resistance Figure 5 The hot laminated layer described in Example 1 shows nearly six times improvement over the laminate described in the Comparative Example which was pressed only at room temperature. In addition, in contrast to the Comparative Example, the hot laminate is less dependent on the applied pressure during the electrochemical testing. For example, when the applied pressure is increased from 0.0 kgf / cm 2 Increase to 0.3kgf / cm 2 It decreased by less than 3%.

[0099] from Figure 5 It can be seen that when the negative electrode of Comparative Example 1 is used, the interface resistance (R1) is a very high 50000Ω when no pressure is applied, while the interface resistance (R2) is very high when 0.3 kgf / cm2 is applied. 2The interface resistance (R2) is 40000Ω when the pressure is 1.5V. Therefore, it can be found that the pressure changes greatly when the symmetrical cell is pressurized or not, and the high pressure should be maintained continuously during battery operation (battery driving).

[0100] However, when the symmetrical cell of Example 1 was used, the interface resistance (R1) when no pressure was applied was 8000Ω, which was significantly lower than that of Comparative Example 1. 2 The interface resistance (R2) when the pressure is 0.3 kgf / cm2 is 7800Ω, which is significantly lower than the interface resistance of Comparative Example 1 when the same pressure is applied to the symmetrical cell. 2 The change rate of the interface resistance value when the pressure is increased by only about 3%, and it can be found that the interface resistance is substantially the same regardless of whether the pressure is applied. In the negative electrode-glass electrolyte layer laminate according to the exemplary embodiment, the lithium metal-containing negative electrode and the glass electrolyte layer are laminated with excellent bonding, and therefore, separate pressurization for maintaining bonding is not required during battery operation.

[0101] While exemplary embodiments have been shown and described above, it will be apparent to those skilled in the art that modifications and variations may be made without departing from the scope of the invention as defined in the appended claims.

Claims

1. A negative electrode-glass electrolyte layer laminate, comprising: a negative electrode and a sulfide glass electrolyte layer on at least one surface of the negative electrode, The negative electrode comprises a surface-passivated lithium-containing metal foil, which is directly laminated on the surface of the sulfide glass electrolyte layer. When 0.3 kgf / cm is applied to the laminate 2 When the pressure is increased, the interface resistance between the lithium-containing metal foil and the sulfide glass electrolyte layer is reduced by less than 10%. 2 . The negative electrode-glass electrolyte layer laminate according to claim 1 , wherein the negative electrode-glass electrolyte layer laminate has no pores in an interface between the negative electrode and the sulfide glass electrolyte layer. 3 . The negative electrode-glass electrolyte layer laminate according to claim 1 , wherein the interface between the negative electrode and the glass electrolyte layer has a laminate layer composed of elemental components containing lithium metal and sulfide glass electrolyte. 4 . The negative electrode-glass electrolyte layer laminate according to claim 3 , wherein the thickness of the laminate layer is greater than 0 μm and is about 20 μm or less. 5 . The negative electrode-glass electrolyte layer laminate according to claim 3 , wherein the thickness of the laminate layer is about 0.1 μm or more and about 5 μm or less. 6 . The negative electrode-glass electrolyte layer laminate according to claim 1 , wherein the glass electrolyte layer is a bulk electrolyte layer. 7 . The negative electrode-glass electrolyte layer laminate according to claim 1 , wherein the glass electrolyte layer has a thickness of 200 μm or less.

8. A method for manufacturing a negative electrode-glass electrolyte layer laminate, the method comprising: Provide sulfide glass electrolyte sheets; Providing a lithium-containing metal foil having a passivated surface; laminating the sulfide glass electrolyte sheet onto the passivated surface of the lithium-containing metal foil; and applying heat and pressure to laminate the lithium-containing metal foil and the glass electrolyte membrane; Wherein the homologous temperature of the lithium-containing metal foil measured adjacent to the interface with the sulfide glass electrolyte is in the range of 0.85 to <1. 9 . The method for manufacturing a negative electrode-glass electrolyte layer laminate according to claim 8 , wherein the lamination is performed so that the homologous temperature is about 0.85, or about 0.9, or about 0.

95.

10. The method for producing a negative electrode-glass electrolyte layer laminate according to claim 8, wherein at 0.05 kgf / cm 2 Up to 0.3kgf / cm 2 The lamination is performed within a pressure range of 200 ℃ to 500 ℃.

11. The method for producing a negative electrode-glass electrolyte layer laminate according to claim 8, wherein: The lamination is performed for 5 to 30 minutes.

12. An all-solid-state secondary battery, comprising: The negative electrode-glass electrolyte layer laminate according to claim 1; and positive electrode.

13. The all-solid-state secondary battery according to claim 12, further comprising: The glass electrolyte layer of the negative electrode-glass electrolyte layer laminate and the solid electrolyte layer between the positive electrode.